Vegetables galore in Kiribati - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Positive changes in diet have been reported by a programme addressing vitamin A deficiencies, a major health problem in Kiribati and Tuvalu. The Pacific Regional Agricultural Project (PRAP) has noted a change of attitude towards vegetables over the...